Eye-selfie to resolve the enigmatic diagnosis of transient "eye spot". Issue 1 (January 2022) - Iacono, Pierluigi; Saviano, Sandro; Parravano, Mariacristina; Varano, Monica; Battaglia Parodi, Maurizio
Purpose: To describe two cases of Cobb's tufts in apparently healthy subjects. Methods: Observational case series. Results: Two patients reporting sudden vision loss, with subsequent complete recovery, underwent a complete ophthalmological examination, including iris fluorescein angiography. Both patients took an "eye-selfie" using their smartphone to provide evidence of the iris bleeding. Iris fluorescein angiography confirmed the presence of iris neovascular tufts at the pupillary margin. Conclusion: Diagnosis of Cobb's tufts can frequently be challenging. The two patients' astute action in taking photographs of the eye enabled the condition to be promptly identified.